Penguatan Usaha Budidaya Udang Vaname (Litopenaeus vannamei) melalui Pendampingan Penerapan CBIB di Pengambengan, Jembrana, Bali - Arie Kiswanto; Ilham Ilham; Mohsan Abrori; I Nyoman Sudiarsa; Andina Chairun Nisa; Annisa Khairani Aras; Diah Ayu Satyari Utami; Liga Insani; Desy Febrianti; Amiqatul Fikriyah; Diklawati Jatayu; Anik Kusmiatun (Institut Pertanian Bogor, 2026)
Good Aquaculture Practices (GAqP) represent a controlled aquaculture management system designed to ensure food safety, product quality, and environmental sustainability. The dissemination of GAqP principles to aquaculture farmers can be achieved through technical training and intensive mentoring programs. In this context, the Aquaculture Study Program of Jembrana Marine and Fisheries Polytechnic implemented a Community Service Program aimed at promoting the adoption of GAqP and enhancing the knowledge and technical capacity of Pacific white shrimp (Litopenaeus vannamei) farmer groups in Pengambengan Village, Bali. The program focused on strengthening community-based shrimp farming enterprises through the application of environmentally friendly technologies, efficient resource utilization, and strategies to improve both the quality and quantity of production. Through technical training and intensive assistance, participants acquired knowledge and practical skills related to optimal pond management, shrimp health monitoring, feed management, and the implementation of operational standards in accordance with GAqP requirements. The extension and mentoring activities carried out under the community service program were effective in improving participants’ understanding of GAqP implementation in Pacific white shrimp farming. This improvement was demonstrated by a significant increase in the average test score, from 56 ± 6.9 in the pre-test to 96 ± 6.9 in the post-test. The implementation of GAqP through continuous mentoring activities under the Community Service Program from 2019 to 2024 contributed to the development of more productive and sustainable Pacific white shrimp farming enterprises among the assisted community groups in Pengambengan Village. Furthermore, the program generated positive economic outcomes by enhancing the income of participating farmers.